2017
DOI: 10.1016/j.burns.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Burns and long-term infectious disease morbidity: A population-based study

Abstract: These findings suggest that burn has long-lasting effects on the immune system and its function. The increase in infectious disease in three different epithelial tissues in the burn cohort suggests there may be common underlying pathophysiology. Further research to understand the underlying mechanisms are required to inform clinical interventions to mitigate infectious disease after burn and improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 41 publications
1
19
0
2
Order By: Relevance
“…While a growing body of work indicates that serious injury suppresses immune function [ 8 , 10 12 ] recent animal-based research found long-term immune dysfunction after non-severe burn injury [ 13 ]. These results were supported by our previous study, which found increased infectious disease morbidity among burn patients after both minor and severe burns, for a prolonged period after discharge, when compared with an age gender matched cohort of uninjured people [ 14 ]. In this study, burn patients were found to have significantly elevated rates of first-time infectious disease admissions after discharge with rates reducing in magnitude from five times higher during the first 30 days post-discharge, 1.7 times higher for the remainder of the first year and 1.4 times higher for the following 9 years.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…While a growing body of work indicates that serious injury suppresses immune function [ 8 , 10 12 ] recent animal-based research found long-term immune dysfunction after non-severe burn injury [ 13 ]. These results were supported by our previous study, which found increased infectious disease morbidity among burn patients after both minor and severe burns, for a prolonged period after discharge, when compared with an age gender matched cohort of uninjured people [ 14 ]. In this study, burn patients were found to have significantly elevated rates of first-time infectious disease admissions after discharge with rates reducing in magnitude from five times higher during the first 30 days post-discharge, 1.7 times higher for the remainder of the first year and 1.4 times higher for the following 9 years.…”
Section: Introductionsupporting
confidence: 84%
“…In this study, burn patients were found to have significantly elevated rates of first-time infectious disease admissions after discharge with rates reducing in magnitude from five times higher during the first 30 days post-discharge, 1.7 times higher for the remainder of the first year and 1.4 times higher for the following 9 years. Respiratory, skin and soft tissue and gastrointestinal infections were the most commonly observed primary reason for a post-injury infectious disease hospital admission in this burn cohort [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bu infeksiyonların yayılımının artması sonucunda, kısmi kalınlıklı yara tam kat yaraya dönüşebilir. İnvaziv yara infeksiyonlarında kültür sonucuna göre sistemik antibiyotik kullanımı gereklidir (16).…”
Section: Akutunclassified
“…In the world, approximately 265,000 deaths occur annually, which represents a severe public health problem [1]. Studies have been reporting that skin injuries are related to microbial colonization, suppressing the immune function predisposing the people to infectious diseases [2]. Hassen, et al [3], reported that the most commonly isolated bacteria in burn children were methicillin-susceptible Staphylococcus aureus (MSSA, 57.7%), Pseudomonas aeruginosa (35.9%), and Enterobacter cloacae (26.9%) wild types [3].…”
Section: Introductionmentioning
confidence: 99%